Effects of dietary energy level on lipid metabolism‐related gene expression in subcutaneous adipose tissue of Yellow breed × Simmental cattle. (30th November 2014) - Zhang, Haibo; Zhang, Xiangfei; Wang, ZhiSheng; Dong, Xianwen; Tan, Cui; Zou, Huawei; Peng, Quanhui; Xue, Bai; Wang, Lizhi; Dong, Guozhong
Abstract This study was conducted to estimate the effect of dietary energy level on lipid metabolism‐related gene expression of subcutaneous adipose tissue in Yellow breed × Simmental cattle. The experiment was conducted for 60 days. The results showed that final weight, average daily gain, average backfat thickness, (testicles + kidney + pelvic) fat percentage and subcutaneous fat percentage in the high and medium energy groups were significantly higher than in the low‐energy group but that the feed conversion ratio was significantly lower. The glucose, triglycerides, cholesterol, high‐density lipoprotein and low‐density lipoprotein in the high‐energy group were significantly higher than in the low‐energy group. With dietary energy increasing the activities of lipoprotein lipase (LPL), fatty acid synthase (FAS) and acetyl‐CoA carboxylase (ACC) significantly increased, whereas hormone‐sensitive lipase (HSL) and carnitine palmitoyltransferase‐1 (CPT‐1) significantly diminished. Peroxisome proliferator‐activated receptor γ (PPARγ), LPL, FAS, sterol regulatory element binding protein 1 (SREBP‐1), ACC, stearoyl‐CoA desaturase (SCD) and adipocyte‐fatty acid binding proteins (A‐FABP) gene expression were significantly increased by dietary energy increasing, and HSL and CPT‐1 gene expression were significantly decreased. These results indicated that with dietary energy increasing, the subcutaneous fat accumulation mainly increased due to adipose tissue lipogenic gene expression and decreased lipolytic gene expression.